2012
DOI: 10.1371/journal.pone.0049174
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanisms of Cell Rigidity Sensing: Insights from a Computational Model of Actomyosin Networks

Abstract: Cells modulate themselves in response to the surrounding environment like substrate elasticity, exhibiting structural reorganization driven by the contractility of cytoskeleton. The cytoskeleton is the scaffolding structure of eukaryotic cells, playing a central role in many mechanical and biological functions. It is composed of a network of actins, actin cross-linking proteins (ACPs), and molecular motors. The motors generate contractile forces by sliding couples of actin filaments in a polar fashion, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 40 publications
9
57
0
Order By: Relevance
“…Consistent with prior computational models (25), this equation shows that the contractile stress σ a gives rise to either the buildup of a contractile tension σ (if clamped boundary conditions allow no strain) or a contractile strain rate σ a =ð2τ α EÞ proportional to α myo =τ myo [if free boundary conditions allow strain but not tension buildup (e.g., in the case of superprecipitation in vitro) (33)] or a combination of these. We then asked whether this simple rheological law for the actomyosin cortex could explain the behavior of cells in our microplate experiments (Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with prior computational models (25), this equation shows that the contractile stress σ a gives rise to either the buildup of a contractile tension σ (if clamped boundary conditions allow no strain) or a contractile strain rate σ a =ð2τ α EÞ proportional to α myo =τ myo [if free boundary conditions allow strain but not tension buildup (e.g., in the case of superprecipitation in vitro) (33)] or a combination of these. We then asked whether this simple rheological law for the actomyosin cortex could explain the behavior of cells in our microplate experiments (Fig.…”
Section: Resultssupporting
confidence: 75%
“…The crucial dependence of this behavior on the fact that cross-linkers have a short lifetime is reminiscent of the model of muscle contraction by Huxley (22), in which the force dependence of muscle contraction rate is explained by the fact that, for lower muscle force and higher contraction speed, the number of myosin heads contributing to filament sliding decreases in favor of those resisting it transiently before they unbind. Although it is known that many molecules associated with actomyosin exhibit stress-dependent dynamics (23,24) and can lead to microscale response to rigidity (25,26), collective effects govern the linear response of actomyosin and are sufficient to explain the observations in both the model by Huxley (22) and this model: we show that force-dependent binding kinetics tune the system's efficiency without essential alterations to its behavior, as Huxley (22) noted himself. Despite very dissimilar organization of actomyosin in muscles, where it forms well-ordered sarcomeres, and nonmuscle cell cortex, where no large-scale patterning is observed, we show that similar mechanisms explain their motor properties.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…These stalling events may occur for several reasons such as high forces, arrival at barbed ends or blocking due to lack of binding sites. These phenomena and their role in cell mechanosensing were previously explored in (Borau et al 2012). In that work, using a Brownian dynamics computational model, we found that although the cause for motor stalling depends on the extracellular matrix (ECM) compliance, the number of stalled motors and the stalling evolution with time is practically independent of ECM stiffness.…”
Section: Constitutive Lawmentioning
confidence: 98%
“…α:false[0,Tfalse]R and interpret α ( t ) as the level of motor stalling, that is to say, the ratio of myosin molecules that are stalled, with α =1 meaning that the cell has reached equilibrium (Borau et al 2012). Therefore, this ratio takes on various values corresponding to the range 0 ≤ α ( t ) ≤ 1.…”
Section: Constitutive Lawmentioning
confidence: 99%